The Association Between IL-2 Gene (RS2069763 (Single Nucleotide Polymorphism and Type 2 Diabetes Mellitus in Iraqi Patients - Al-Malkey, Maysaa Kadhim (Iraqi Journal of Science, 2020)
This research attempts to find the association between single nucleotide polymorphism (SNP) of IL2+166 gene (rs2069763) and type 2 diabetes mellitus (T2DM) in a sample of Iraqi patients. A total of 44 patients and 55 apparently healthy volunteers were genotyped for the SNP using polymerase chain reaction test. Three genotypes (GG, GT, and TT) corresponding to two alleles (G and T) were found to have SNP. Both study groups’ genotypes had a good agreement for the analysis of Hardy-Weinberg Equilibrium. The results revealed increased frequencies between the observed and expected GG and TT genotypes and IL2+166 SNP T allele in T2DM patients (40.9 vs. 40.0 %; OR = 1.04; 95% CI, 0.47 - 2.31), whereas the values in the control group were 11.4 vs. 9.1 %; OR = 1.28; 95% CI, 0.35 - 4.68. Nevertheless, both variations did not reach a significant level. In the Iraqi population, the IL2+166 SNP was not associated with T2DM and, therefore, no association with its etiopathogensis was found.